How Does Bank Competition Affect Solvency, Liquidity and Credit Risk? : Evidence from the MENA Countries - Almarzoqi, Raja (IMF Working Papers; Working Paper ;, 2015)
The paper analyzes the relationship between bank competition and stability, with a specific focus on the Middle East and North Africa. Price competition has a positive effect on bank liquidity, as it induces self-discipline incentives on banks for the choice of bank funding sources and for the holding of liquid assets. On the other hand, price competition may have a potentially negative impact on bank solvency and on the credit quality of the loan portfolio. More competitive banks may be less solvent if the potential increase in the equity base-due to capital adjustments-is not large enough to compensate for the reduction in bank profitability. Also, banks subject to stronger competitive pressures may have a higher rate of nonperforming loans, if the increase in the risk-taking incentives from the lender's side overcomes the decrease in the credit risk from the borrower's side. In both cases, country-specific policies for market entry conditions-and for bank regulation and supervision-may significantly affect the sign and the size of the relationship. The paper suggests policy reforms designed to improve market contestability and to increase the quality and independence of prudential supervision.